2016
DOI: 10.1097/bsd.0b013e31829046af
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Surgical Treatment for Symptomatic Anterior Cervical Osteophytes

Abstract: Symptomatic ventral cervical osteophytes can be successfully treated by surgery. In the majority of patients, osteophytes do not regrow significantly in the long term, precluding the need for prophylactic instrumented fusion after osteophyte resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…24,53,[55][56][57] If the extrinsic cause is more prominent, in case of more severe problems and impairment of the quality of life, surgical resection of the osteophytes via a standard anterior approach is performed. 4,[24][25][26][27][28] This can achieve sufficient improvement with a low morbidity rate 4,17 ; regression of the symptoms can occur quickly (in up to 2 weeks) but may sometimes take months. 21,26,27,30,58 The results are more limited the more advanced the changes in the esophagus itself are (inflammation, fibrosis, impaired peristalsis, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,53,[55][56][57] If the extrinsic cause is more prominent, in case of more severe problems and impairment of the quality of life, surgical resection of the osteophytes via a standard anterior approach is performed. 4,[24][25][26][27][28] This can achieve sufficient improvement with a low morbidity rate 4,17 ; regression of the symptoms can occur quickly (in up to 2 weeks) but may sometimes take months. 21,26,27,30,58 The results are more limited the more advanced the changes in the esophagus itself are (inflammation, fibrosis, impaired peristalsis, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…66 Recurrent cervical osteophytes are rare, develop slowly, and have been described in long-term follow-up over 10 years. 4,17,[29][30][31] Routine additional fusion is therefore discussed not only due to possible operationinduced instability, but also because segmental mobility can promote the further development of osteophytes. 9,[29][30][31] There is experience in the prophylaxis of ossification in particular in connection with the implantation of hip replacements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] When these bony growths become large enough, they can lead to dysphagia, dysphonia, dyspnea, and obstructive sleep apnea. 3,[6][7][8] Previous studies have shown that less than 1% of cervical osteophytes lead to dysphagia, and only 1.7% of cases of dysphagia are caused by cervical osteophytes. 3,5,9 Osteophytes may cause dysphagia via multiple mechanisms, including mechanical compression of the esophagus, interference with normal epiglottis movement, compression of the Auerbach's myenteric plexus, and the induction of inflammation and edema about the esophagus, which can lead to fibrosis and adhesions, preventing normal motility and causing cricopharyngeal spasm.…”
Section: Introductionmentioning
confidence: 99%
“…Complications associated with osteophyte formation are numerous (dysphagia, thoracic aortic compression, vena cava obstruction, nerve root compression) and affect most structures located in close-proximity to the spine. As a consequence, they are generally viewed as a degenerative condition and can be removed surgically by traditional or minimally invasive techniques during spinal surgery, when they lead to a disability or neurological symptoms [ 1 , 7 ]. Recently, it was suggested that vertebral osteophytes primarily stabilize the spine in bending and increase its resistance in compression [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%